Development of a logistics strategy for the enterprise - Hao, Wang (Харківський національний автомобільно-дорожній університет, 2024)
In this qualification work, the concept of a «logistics strategy» for enterprises has been further developed. The study highlights the multi-level formation of the strategy, which includes time, strategic, integrated, economic, and informational levels. It also refines the substantive components of the process and the primary focus of the logistics strategy-cost reduction combined with the highest level of consumer satisfaction. The methodological approach to justifying the choice of a logistics strategy was improved by incorporating assessments of the enterprise's logistics system and logistics costs. A simulation model for logistics business processes was developed, and the economic efficiency of implementing the logistics strategy was evaluated. Predictive assumptions for the development of the research object – the proposed methodological approaches and practical developments can be used to enhance logistics strategies in enterprises across various industries, particularly in the transport and manufacturing sectors.
Keywords: logistics strategy; enterprises; decision-making process; cost optimization; logistics business processes; simulation modeling; efficiency